Application of comprehensive project training based on Miller “Pyramid” principle in strengthening nursing skills of nursing students - YIN, Hongmei (Chinese Journal of Integrative Nursing, 2023)
Objective To explore the application effect of comprehensive project training based on Miller’s “Pyramid” principle in nursing students’ strengthening training of nursing skills. Methods Convenient sampling method was used to select 112 students from 2 classes of nursing major in 2019 who were about to participate in clinical practice in the hospital. They were randomly divided into observation group (n=56) and control group (n=56). The observation group adopted the comprehensive training method based on Miller’s “Pyramid” principle. The control group used the traditional training method. The two groups of nursing students were compared in theory, skills, comprehensive cases and knowledge, skills application ability test results, evaluation of the two groups of nursing students in training behavior. Results The scores of theoretical knowledge, practical skills, comprehensive cases and application ability assessment in the observation group were higher than those in the control group (P < 0. 01). The behavioral performance evaluation scores of nursing students in the observation group were higher than those in the control group (P < 0. 01). The satisfaction score of nursing students in the observation group was higher than that in the control group(P < 0. 01). Conclusion The comprehensive project simulation training based on Miller "pyramid" principle is beneficial to improve the theoretical knowledge and operation ability of nursing students, improve the comprehensive ability of nursing students, standardize the nursing operation procedures of nursing students, and improve the quality of intensive training. (目的 探讨基于米勒“金字塔”原理的项目综合训练在护生护理技能强化练习中的应用效果。方法 采用便利抽样法抽取即将参加临床实习的2019级护理专业2个班级, 共112名护理学生为研究对象, 随机分为观察组56名和对照组56名。对照组采用传统实训练习方法; 观察组采用基于米勒“金字塔”原理的项目综合训练法。比较两组护生理论知识、操作技能、综合案例、临床实际应用能力考核成绩, 评价两组护生训练中的行为表现。结果 观察组理论知识、操作技能、综合案例和临床应用能力考核成绩均高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生行为表现评价分均高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 基于米勒“金字塔”原理的项目综合模拟训练有利于提高护生理论知识和操作技能, 提高护生的综合能力, 能规范护生的护理操作程序, 提高强化实训质量。)